Move to sleep: how exercise timing and intensity shape sleep quality - a narrative review - Mierniczek, Mateusz; Mika, Wiktoria; Mierniczek, Maria; Kotte, Kordian; Gloc, Ewa; Dmowska, Dominika; Bilińska, Aleksandra; Zdebski, Paweł; Mierniczek, Aleksandra (Journal of Education, Health and Sport, 2025)
Background: Sleep and physical exercise represent two fundamental pillars of human health. The relationship between movement and sleep becomes particularly interesting when we consider how timing and intensity work together. While each factor independently affects sleep, their combined influence is increasingly recognized as crucial for understanding how physical activity impacts our nightly rest. Aim: To summarize current evidence on how different times of day and exercise intensities affect sleep quality, latency, and duration in healthy adult populations. Material and Methods: A narrative review was conducted using 32 peer-reviewed articles published in English. Sources were identified from PubMed, Web of Science, Google Scholar, and ScienceDirect. Inclusion criteria focused on healthy adult participants. Results: Exercise in the morning and afternoon was generally related to better sleep, but vigorous activity performed close to nighttime had mixed or bad effects. Moderate-intensity physical activity, especially when done over a long period of time, always made sleep better and made it take longer to fall asleep. Age, chronotype, and fitness level were some of the individual factors that changed the effects that were seen. However, differences in methods between studies, especially in how they measured sleep and how they did exercises, make it hard to compare them directly. Conclusions: Timing and intensity are critical modifiers of the sleep benefits of exercise. While moderate, earlier-in-the-day exercise appears most beneficial, tailored interventions based on individual characteristics may enhance sleep optimization strategies. Future research should prioritize standardized protocols and consider individualized approaches to optimize exercise timing and intensity for sleep health.